Principais aspectos do fundacionalismo na epistemologia contemporânea - Echer, Elizabete Cristina (2022)
The present essay has as its fundamental focus the presentation and discussion of the different internalist Foundationalist Theories. We begin, in the first chapter, with a brief introduction to Epistemology, where we discuss some of the main concepts and epistemological notions that are fundamental for an adequate understanding of the challenges faced by foundationalist theories, including the classic Trilemma of Agrippa. In the following chapters, guiding the rest of the discussion, we focus on the presentation and discussion of Foundationalist theories. Foundationalist theories were portrayed under a Cartesian approach, a revised Classical Foundationalist approach (from BonJour, McGrew and Fumerton), and a moderate Foundationalist approach, portrayed by Pryor and Audi. Finally, a brief account of the Externalist Foundationalism assumed by Goldman is presented.